Re-empaquetando el CLPI: las conexiones globales y el debate sobre el consentimiento indígena para la extracción industrial de recursos - Szablowski, David (2010)
In this paper, I propose to examine how rival global governmentalprojects are asserted and contested by decentralized networks thatlink actors operating at different scales. I argue that Tsing’s notionof «travelling packages» provides a useful way of conceptualizingthe means by which elements of these projects are diffused, translated,taken up, and adapted into different localities around theworld. I explore these dynamics in relation to the contestation of agovernance model based on the principle that the free, prior andinformed consent (FPIC) of an indigenous people is required toauthorize actions that may affect upon indigenous territory or indigenousrights. Through the assertion of different versions of FPIC,networked actors are contesting the nature and shape of corporatesocial responsibility, the authority of the state, and the significanceof indigenous governance. I propose to explore the implicationsof different packaging strategies on the contestation between rivalgovernance models and on their propensity for uptake in local sites.